The Use and Understanding of Mild Cognitive Impairment in Routine Specialist Care: A Survey Among German Memory Clinics - Gloria S. Benson; Claudia Bartels; Feride Stamatis; Michael Belz; Hermann Esselmann; Lutz Frölich; Lucrezia Hausner (Geriatrics)
Objectives: Mild cognitive impairment (MCI) is a heterogeneous clinical syndrome and is important for the diagnosis and management of Alzheimer’s disease (AD). With the expansion of biomarker-based diagnostics, the aim of this study is to clarify the current attitudes towards and the use of MCI, and MCI due to AD, in German memory clinics. Methods: An online survey (50 items) was performed in 2022 among specialized clinicians (N = 45) in German memory clinics to assess the use of MCI and biomarkers in current diagnosis and treatment. Attitudinal and frequency items were assessed with a five-point numeric scale (strongly disagree = 1 to completely agree = 5 and never = 1 to always = 5, respectively). Results: All respondents used MCI as a clinical diagnosis. The benefits of diagnosing MCI were labeling deficits as disease symptoms (M = 4.4, SD = 0.7), improving coping with symptoms (M = 4.1, SD = 0.9), and motivating risk reduction activities (M = 4.0, SD = 0.9). Overall, 37 respondents used specialized diagnostic criteria for MCI due to AD, and all had access to biomarker diagnostics. Patients with MCI due to AD received more frequent counseling on memory training (p < 0.001), other non-pharmacological treatments (p < 0.001), and antidementive drug treatment (p < 0.001) than patients with MCI of other etiologies. Acetylcholinesterase inhibitors were prescribed significantly more frequently to patients with MCI due to AD (p < 0.001) compared to other MCI patients. Conclusions: MCI is commonly used as a clinical diagnosis in German memory clinics. AD biomarker assessment is well established and influences patient counseling and treatment recommendations.